166k views
2 votes
I need help to solve it, be serious if you don't know don't answer please.

I need help to solve it, be serious if you don't know don't answer please.-example-1
User Pedrobern
by
4.7k points

1 Answer

6 votes

k^2-8k+20=8
k^2-8k+12=0
k^2-8k=-12
k^2-8k+16=-12+16
(k-4)^2=4

then k-4=2 or k-4=-2

and we have that k=6 and k=2, are the two answers for the equation.

if we replace k=2 in the first equation


(2)^2-8(2)+20=4-16+20=-12+20=8

which makes the equation true for k=2, then is we replace k=6 in the first equation:


(6)^2-8(6)+20=36-48+20=-12+20=8

then the equation holds for k=6 too.

the second equation is:


2=\sqrt[]{-4-x}

then


4=-4-x
x=-4-4

finally


x=-8

if we replace x=-8 in the second equation


\sqrt[]{-4-(-8)}=\sqrt[]{-4+8}=\sqrt[]{4}=2

then the equation holds for x=-8.

User Gepser Hoil
by
4.8k points